Abnormal Returns and Stock Price Movements: Some Evidence from Developed and Emerging Markets - Guglielmo Maria Caporale; Alex Plastun (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper investigates the impact of abnormal returns on stock prices by using daily and hourly data for some developed (US, UK, Japan) and emerging (China, India) markets over the period 01.01.2010-01.01.2020. Average analysis, t-tests, CAR and trading simulation methods are used to test the following hypotheses: H1) abnormal returns can be detected before the end of the day; H2) there are price effects on the day after abnormal returns occur; H3) these effects are different for developed vis-à-vis emerging markets; H4) they can be used to generate profits from intraday trading. The results suggest that there is a 2-hour window before close of business to exploit momentum effects on days with abnormal returns. On the following day momentum effects occur after positive abnormal returns, and contrarian (momentum) effects in the case of developed (emerging) stock markets after negative abnormal returns. Trading simulations show that some of these effects can be exploited to generate abnormal profits with an appropriate calibration of the timing parameters.
Keywords: G12; G17; C63; 330; stock market; anomalies; momentum effect; contrarian effect; abnormal returns